Performance Based Exploration of Generative Design Solutions Using Formex Algebra. (September 2014) - Khodadadi, Anahita; von Buelow, Peter
This paper illustrates the use of a computational form-finding method called ParaGen which aids the designer in the exploration of arrays of good solutions. Although the method is guided by a multi-objective optimization program, the goal is to promote the exploration of the solution space based on designer selected combinations of performance objectives. The digital form generation of the bridges is carried out using Formian, a program which uses Formex algebra to describe a wide array of geometric configurations. This form generation is linked to structural simulation and design software (STAAD.Pro) to determine performance values. Finally, ParaGen is used to build a database of all solutions and guide the exploration based on performance values. Using this database, both visual and numeric characteristics are explored.